A Taiwanese study on real-world evidence with vortioxetine in patients with major depression in Asia (TREVIDA). (2nd December 2021) - Yang, Yen Kuang; Chen, Cheng-Sheng; Tsai, Chia-Fen; Chang, Chia-Ming; Lai, Te-Jen; Lee, Chun-Te; Lin, Chih-Chien; Lan, Tsuo-Hung; Herr, Keira Joann
Abstract: Objective: The TREVIDA study aimed to evaluate vortioxetine for the treatment of major depressive disorder (MDD) in Taiwanese adults. Methods: Patients with active depressive episode were recruited in this non-interventional, prospective, multi-site study conducted between June 2019 and August 2020 in Taiwan. Patient eligibility was independent of the physician's decision to prescribe vortioxetine for an MDD episode. Vortioxetine was initiated on the first visit. Depression severity, cognitive function, work productivity, functioning and safety were evaluated over 3 months. Results: Overall, 242 patients were analyzed. At baseline, 70.7% and 90.4% of patients had moderately severe-to-severe depression based on PHQ-9 (Patient Health Questionnaire-9) and TDQ (Taiwanese Depression Questionnaire), respectively. By Month 3, significant improvements from baseline in depression severity (mean [SD] changes in PHQ-9, TDQ and CGI-S [Clinical Global Impression–Severity]: −6.3 [7.3]; −13.2 [14.0]; −1.5 [1.3], respectively), cognitive function (mean [SD] change in PDQ-D: −8.0 [17.5]), functioning (mean [SD] change in SDS: −5.4 [7.6]), and presenteeism (38.9% from 56.3%), work productivity loss (40.9% from 58.7%) and activity impairment (43.2% from 61.0%) were observed ( p  < .001 for all). By month 3, patient-reported (PHQ-9) response and remission rates were 43.4% and 52.9%, respectively; physician-reported (CGI-S) response and remission rates were 29.0% and 31.6%, respectively. Vortioxetine was well-tolerated and no unexpected side effects were reported. Conclusions: Vortioxetine reduced depression severity and improved cognitive function, work productivity, and functioning in Taiwanese patients with MDD in the real-world setting. Vortioxetine was well-tolerated in this Taiwanese population.